URGENSI PERLINDUNGAN HAK KONSTITUSI ANAK OLEH PEMERINTAH DAERAH KABUPATEN SAMBAS - Wiwin Guanti (AL-SULTHANIYAH, 2021)
The high number of child cases in the last 3 (three) years tends to increase, especially sexual violence against children in sambas. Local governments have a very important role in child protection as stated in the Child Protection Act. Law Number 23 of 2014 concerning Regional Government and Government Regulation Number 18 of 2016 concerning Regional Apparatuses strengthens that child protection matters are a mandatory regional affair. The role of DP3AP2KB in carrying out its duties is in the form of prevention and handling of child sexual violence in Sambas Regency. The results of research related to the role of DP3AP2KB in its implementation, DP3AP2KB through Counseling and Legal Aid activities have met the existing standard operating procedures. However, the assistance provided was not optimal because the DP3AP2KB party rarely attended during the trial. The socialization carried out is also considered not very effective because of the high rate of sexual violence against children. There are obstacles such as budget and human resources. There is cooperation with other agencies related to child protection